To compare and contrast the effects of dietary supplements between dvit cardio and its competitor brand - Vyas, Sonal (International Journal of Research in Medical Sciences, 2020)
Background: Nutraceuticals are the organically formed by traditional foods, but are consumed in the form pills, capsules or liquids. Dvit Cardio is a nutraceutical that has been proven to be a dietary supplement beneficial for the general as well as the diabetic participants. Dvit Cardio is in the form of powder, thus can be consumed easily. It is a multivitamin supplement that adds to the nutritional intake of the users. The objective of the study was to compare the lipid profile outcomes between Dvit Cardio users and competitor brand users. Methods: The study was undertaken with 100 participants who were randomly divided into two groups of 50 each. Group 1 was given Dvit Cardio, and Group 2 was given the competitor brand. The study was performed at Sri Aurobindo Institute of Medical Sciences, Indore. Results: There was a statistically significant difference between the two groups with regards to the triglyceride level. Further, there was a statistically significant difference among the two groups with regards to HDL Cholesterol level. Also there was a statistically significant difference among the two groups with regards to LDL Cholesterol level and Hb1Ac % level. Conclusions: It was found that Dvit Cardio had positive health impact on the lipid profile parameters of the participants included in the study as compared to the competitor brand. It was also found that Dvit Cardio was beneficial for diabetic patients owing to its sugar-free properties.